Theoretical analysis on bio-magnetic Casson hybrid nanofluid blood flow through a stenotic artery with a heat source/sink - Sangapatnam, Suneetha; Ramasekhar, Gunisetty; Chakravarty, Anusuiya; Pallapu, Venugopal (Archives of Thermodynamics, 2026)
The current study focuses on the numerical analysis of magnetohydrodynamic Casson hybrid nanofluid blood flow carrying hybrid nanoparticles through a porous stenotic artery. To improve thermal conductivity and flow management in the presence of a heat source/sink, gold-silver nanoparticles are suspended in the base fluid (blood). The governing highly nonlinear differential equations for momentum and energy are solved using MATLAB's bvp4c solver, ensuring high accuracy and stability. The effects of various physical parameters, including the magnetic parameter, permeability, curvature, Casson parameter, Eckert number, and heat source/sink parameter, are examined on the velocity, temperature, skin friction, and Nusselt number profiles. The results indicate that higher magnetic field strength and permeability reduce velocity due to Lorentz and frictional resistance, while increases in curvature and the Casson parameter enhance the flow rate. The temperature distribution is notably elevated by magnetic forces, viscous dissipation, and internal heating, with hybrid nanoparticles contributing to enhanced thermal energy. The correctness of the model is validated by its strong agreement with previously reported results. These findings provide important insights for biomedical applications such as targeted drug delivery, heat-assisted therapies, and blood flow regulation in diseased arteries, offering a reliable computational framework for future research on nanoparticle-assisted magnetohydrodynamic flow through porous biological channels.